Identification of Dynamic Patterns of Personal Positions in a Patient Diagnosed With Borderline Personality Disorder and the Therapist During Change Episodes of the Psychotherapy - Mellado, Augusto; Martínez, Claudio; Tomicic, Alemka; Krause, Mariane (Frontiers in Psychology, 2022)
Dynamic patterns are identified in voices and personal positions of a patient diagnosed with Borderline Personality Disorder (BPD) and the therapist, in change episodes during long-term psychotherapy. This case study considered the first stage of qualitative analysis where change episodes of the patient were traced through the Change Episodes Model. Later, through the Model of Analysis of Discursive Positioning in Psychotherapy [MAPP], voices and personal positions of the patient and her therapist were identified in each of change episodes. In the second stage of quantitative analysis, dynamic patterns in voices and personal positions were established, accounting of hypothetical attractors using the Space State Grid [SSG] technique in each of the three different levels of subjective elaboration that constitute the change episodes. The analyses established differentiated dynamic patterns in the change episodes, coherent with the patient's change process, and the formation of propositive/reflective specific patterns as the patient evolved in their three different levels of subjective elaboration. Results suggest that a subjective transformation process is displaying, and this is manifested in the different voices and personal positions that emerge as the change episodes evolve. The identified dynamic patterns can be considered non-linear subjective exchanges between patient and therapist throughout the psychotherapy.